Différenciations adaptatives, palliatives et différenciations égalisatrices : l'exemple de l'apprentissage de la lecture - Sandrine Garcia
The article questions the vagueness and ambiguities surrounding the institutional definitions of differentiation as an adaptation to differences between pupils. Based on several fieldwork studies, it shows that the practical constraints faced by teachers lead, in the absence of a clearer definition of the stakes of differentiation, to their adjustment to pupils' initial level. The paper distinguishes between adaptive and mitigating differentiations, which both raise questions. In order to reduce inequalities, it describes an approach experienced in literacy teaching to argue in favour of levelling differentiation.